2022
DOI: 10.1128/spectrum.01870-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of QuantiFERON-TB Gold In-Tube and QuantiFERON-TB Gold-Plus in the Diagnosis of Mycobacterium tuberculosis Infections in Immunocompromised Patients: a Real-World Study

Abstract: This study evaluated the performance of QFT-GIT and QFT-Plus in the diagnosis of M. tuberculosis infection in immunocompromised patients and found that QFT-Plus may detect more LTBI than QFT-GIT does in patients receiving long-term immunosuppressant therapy. We believe that our study makes a significant contribution to the literature because it highlights the different diagnostic accuracies of QFT-GIT and QFT-Plus in different subpopulations of immunocompromised and immunocompetent pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, Xu YZ found that IGRA may detect more LTBI in immunocompromised patients. 20 IGRA cannot distinguish between active TB and LTBI because it cannot measure the infection itself, which have important limitations and poor predictive value for active TB in CKD patients. Therefore, selecting a test with better performance may help early detection and better treatment of TB in patients with a high risk of developing active TB.…”
Section: Discussionmentioning
confidence: 99%
“…However, Xu YZ found that IGRA may detect more LTBI in immunocompromised patients. 20 IGRA cannot distinguish between active TB and LTBI because it cannot measure the infection itself, which have important limitations and poor predictive value for active TB in CKD patients. Therefore, selecting a test with better performance may help early detection and better treatment of TB in patients with a high risk of developing active TB.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of indeterminate results in immunocompromised patients is higher than that observed in immunocompetent individuals [62]. In addition, the indeterminate results determined by QFT-GIT were higher compared with QFT-Plus [62]. Since our samples were transported within the specified time interval and the proper procedure was followed during the specimens' storage and processing, the possibility of a wrong technical practice is potentially excluded.…”
Section: Discussionmentioning
confidence: 88%
“…An indeterminate result may be related to immunosuppression associated with older age and underlying diseases or due to some technical errors [61]. The rate of indeterminate results in immunocompromised patients is higher than that observed in immunocompetent individuals [62]. In addition, the indeterminate results determined by QFT-GIT were higher compared with QFT-Plus [62].…”
Section: Discussionmentioning
confidence: 99%
“…HIV impacts the QuantiFERON-TB Gold In-Tube test (QFT-GIT) less than it does the ELISPOT (T SPOT-TB) 24 25. The QFT Gold Plus (QFT-Plus) and its forerunner, the QFT-GIT, have concordant performance 26 27. This paper presents the results of a study that sought to estimate TB infection prevalence among PLHIV using the QFT-Plus assay in a high TB burden context.…”
Section: Introductionmentioning
confidence: 99%